2021
DOI: 10.1016/j.ijbiomac.2021.05.155
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan, alginate, hyaluronic acid, gums, and β-glucan as potent adjuvants and vaccine delivery systems for viral threats including SARS-CoV-2: A review

Abstract: Pathogen transmission is a widespread threat to global human health. Vaccines are very important during the outbreak of a pandemic. Destructive fractures caused by a sudden outbreak of COVID-19 have spurred vaccine production at an unprecedented rate. The strategy of an effective vaccine delivery system is opening up novel probabilities to make more immunization. Indeed, vaccination is the most successful way to prevent deaths from infectious diseases. In order to optimal immune response production or improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Previous studies indicated the potential of β-glucans in the prevention, treatment, and complications of COVID-19 [14,169,170,[179][180][181][182][183][184][185][186][187][188][189][190][191][192]. Immunomodulatory, antioxidant, neuroprotective, and antithrombotic activities are of particular interest here.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies indicated the potential of β-glucans in the prevention, treatment, and complications of COVID-19 [14,169,170,[179][180][181][182][183][184][185][186][187][188][189][190][191][192]. Immunomodulatory, antioxidant, neuroprotective, and antithrombotic activities are of particular interest here.…”
Section: Discussionmentioning
confidence: 97%
“…[ [188][189][190] 13. β-glucan (from yeast, Saccharomysces cerevisiae) Decreasing platelet activation by increasing TGF-β1 production. Decreasing the concentration of pro-inflammatory cytokines IL-6, which indirectly activates platelets and thrombin production.…”
Section: Modulation and Activation Of Nk-cells T-cells And γδ-T (Gamma Delta T)mentioning
confidence: 99%
“…To date, vaccination is the most effective way to control infectious diseases. The antigen delivery systems or adjuvants are required to promote immune response production or increase the effectiveness of vaccines [ 69 ]. Some natural polymers with antiviral activity have good potential as antiviral agents, adjuvants or delivery systems for antiviral drugs and vaccine formulation development [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that antigen-loaded chitosan NPs produced enhanced phagocytic activity of peritoneal macrophages and neutralised antibody levels against RVFV and IgG levels against RVFV nucleoprotein, in comparison with adjuvant-free RVFV inactivated antigen. These are a few examples among many in which NPs based on natural polymers have been used for the delivery of viral antigens, which have been extensively reviewed by other researchers [151][152][153][154].…”
Section: Polymeric Nanoparticles (Nps)mentioning
confidence: 99%